Improving the technical and economic efficiency of a derivation-type inverter of micro hydro power plant - B. V. Lukutin; M. M. Popov (Омский научный вестник)
This article presents a comparative analysis of the technical and economic efficiency of a derivation-type inverter micro hydro power plant with an energy storage system and an auto-ballasted micro hydro power plant. The authors justify the possibility of saving financial resources by reducing the length of the derivationtype micro hydro power plant's pressure pipeline with an energy storage system. To optimally control the generating and transforming equipment of an autonomous power supply system, a control algorithm is proposed based on criteria for limiting the range of hydrogenerator rotational frequencies and ensuring the rational operating mode of the electric energy storage batteries according to the load's power consumption schedule. The possibility of using the charging current of the electric energy storage battery in combination with traditional resistive ballast to create a braking control moment for the hydrogenerator is justified. The article considers issues related to regulating the rational generated power of the hydrogenerator by aligning the power consumption schedule using electric energy storage systems, which allows reducing the length of the pressure pipeline and, consequently, capital costs. Thus, the article represents a comprehensive analysis of the technical and economic efficiency and optimal control of a derivation-type inverter micro hydro power plant with an energy storage system, which can be used in the design and operation of similar power supply systems.